Small Cell (Neuroendocrine) Carcinoma of the Prostate: Etiology, Diagnosis, Prognosis, and Therapeutic Implications-A Retrospective Study of 30 Patients From the Rare Cancer Network - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Within the framework of the Rare Cancer Network Study, we examined 30 patients suffering from small cell neuroendocrine prostate cancer, either in an early/localized or an advanced/metastatic stage. Patients were treated with cisplatin-based chemotherapy, with or without pelvic radiotherapy. Two patients with early disease achieved complete remission for a duration of 19 and 22 months. Three patients with advanced disease achieved complete remission for 6, 7, and 54 months, respectively. Twenty-five patients succumbed to massive local and/or distant failure. No patient presented with brain metastases as the initial site of relapse. Small cell neuroendocrine prostate carcinoma is a very aggressive disease with a poor prognosis, even in its localized form. Despite initial response, the common cisplatin-based chemotherapy plus radiotherapy failed to improve Outcome markedly. Improvement will come from understanding the biology of the disease and integrating new targeted therapies into the treatment of this rare and aggressive tumor.
Keywords: Prostate; Small cell carcinoma; Treatment; LUNG-CANCER; BRAIN METASTASIS; DIFFERENTIATION; ADENOCARCINOMA; EXPRESSION; EXPERIENCE; BENIGN; TUMORS; CHEMOTHERAPY